2022
DOI: 10.1177/00472816221104497
|View full text |Cite
|
Sign up to set email alerts
|

You Shall Not Pass? The Design of Age Gates in an Emerging Cannabis Market

Abstract: Age gates are becoming common on the websites of cannabis dispensaries, following design practices in other controversial industries. Yet, age gates can typically be bypassed through trial and error or basic arithmetic, raising questions over best practices. This study therefore characterized the age gates of dispensaries licensed in the Arizona adult use cannabis program, using a “digital mystery shopper” approach to examine the age gates’ location, appearance, and performance. After presenting the results, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…Although age-gating has been used by other industries (e.g., alcohol), its effectiveness has been questioned by researchers (Barry et al, 2021;Madson, 2022;Williams et al, 2015;Williams & Ribisl, 2012). This should sound the alarm for regulators, policymakers, parents, and industry alike on the need to implement a more effective system to prevent minors from accessing online cannabis marketing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although age-gating has been used by other industries (e.g., alcohol), its effectiveness has been questioned by researchers (Barry et al, 2021;Madson, 2022;Williams et al, 2015;Williams & Ribisl, 2012). This should sound the alarm for regulators, policymakers, parents, and industry alike on the need to implement a more effective system to prevent minors from accessing online cannabis marketing.…”
Section: Discussionmentioning
confidence: 99%
“…Cavazos-Rehg et al (2019) found that among randomly selected retailer websites across the U.S., 75% had no form of age-gating in 2016. In contrast, Madson (2022) found that 90% of retailer websites in Arizona, where age verification is required (Ariz. Rev. Stat.…”
mentioning
confidence: 99%